2014
DOI: 10.14257/ijmue.2014.9.11.31
|View full text |Cite
|
Sign up to set email alerts
|

What Makes Smartphone Users Satisfied with the Mobile Instant Messenger?: Social Presence, Flow, and Self-disclosure

Abstract: Users of smartphone-based Instant Messenger such as Whatsapp, wechet, LINE and KAKAO TALK are

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 16 publications
(16 reference statements)
1
15
0
2
Order By: Relevance
“…It is not uncommon for participants with high social presence to invest more in consuming virtual products [19]. In the previous research, researchers found that when people perceive a high social presence, they have a positive attitude to continue use behavior, such as with online games [12,20], online learning [21], SNS use [1,22], and online shopping [18]. With the connection of online games and SNS platforms, therefore, it is believed that perceived social presence has a direct and indirect effect on the sustainable use intention of MSNG players.…”
Section: Social Presencementioning
confidence: 98%
“…It is not uncommon for participants with high social presence to invest more in consuming virtual products [19]. In the previous research, researchers found that when people perceive a high social presence, they have a positive attitude to continue use behavior, such as with online games [12,20], online learning [21], SNS use [1,22], and online shopping [18]. With the connection of online games and SNS platforms, therefore, it is believed that perceived social presence has a direct and indirect effect on the sustainable use intention of MSNG players.…”
Section: Social Presencementioning
confidence: 98%
“…Os participantes deixavam claro que o fator motivador para que eles utilizassem as RSV estava relacionado às questões financeiras. Os aplicativos Facebook e WhatsApp, possibilitam a troca de mensagens por meio de telefone celular, além do compartilhamento de arquivos de texto, vídeo e áudio, e não possui custo de utilização, basta possuir acesso a um telefone inteligente com conexão à internet (AHARONY, 2015;GAIKAR, 2015;PARK;LEE, 2014).…”
Section: Redes Sociais Virtuais Funclassified
“…Based on the results of statistical tests directly show that IM Reliability (X2) has an influence on the effectiveness of Lecturer Performance (Y). It can be concluded that IM can encourage people, especially lecturer to work more effectively and efficiently (Park, Cho, & Lee, 2014). Using IM can simplifying the assignment of lecturers in teaching, research and community service.…”
Section: Discussionmentioning
confidence: 99%